Bioseparation of Four Proteins from Euphorbia characias Latex: Amine Oxidase, Peroxidase, Nucleotide Pyrophosphatase/Phosphodiesterase, and Purple Acid Phosphatase. (15th October 2011) - Medda, Rosaria; Pintus, Francesca; Spanò, Delia; Floris, Giovanni
Abstract : This paper deals with the purification of four proteins from Euphorbia characias latex, a copper amine oxidase, a nucleotide pyrophosphatase/phosphodiesterase, a peroxidase, and a purple acid phosphatase. These proteins, very different in molecular weight, in primary structure, and in the catalyzed reaction, are purified using identical preliminary steps of purification and by chromatographic methods. In particular, the DEAE-cellulose chromatography is used as a useful purification step for all the four enzymes. The purification methods here reported allow to obtain a high purification of all the four proteins with a good yield. This paper will give some thorough suggestions for researchers busy in separation of macromolecules from different sources.